2022
DOI: 10.1007/s00159-022-00139-w
|View full text |Cite
|
Sign up to set email alerts
|

Fast radio bursts at the dawn of the 2020s

Abstract: Since the discovery of the first fast radio burst (FRB) in 2007, and their confirmation as an abundant extragalactic population in 2013, the study of these sources has expanded at an incredible rate. In our 2019 review on the subject, we presented a growing, but still mysterious, population of FRBs—60 unique sources, 2 repeating FRBs, and only 1 identified host galaxy. However, in only a few short years, new observations and discoveries have given us a wealth of information about these sources. The total FRB p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
112
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(114 citation statements)
references
References 179 publications
2
112
0
Order By: Relevance
“…Repeat bursts from FRB 20180916B (R3) that were detected with LOFAR at low frequencies are also shown here(Pleunis et al 2021). Several of these repeater bursts exceed 100 ms in pulse width, but as noted by both Pleunis et al (2021) andPetroff et al (2022), these events are likely dominated by scattering (unlike the FRBs reported here).…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Repeat bursts from FRB 20180916B (R3) that were detected with LOFAR at low frequencies are also shown here(Pleunis et al 2021). Several of these repeater bursts exceed 100 ms in pulse width, but as noted by both Pleunis et al (2021) andPetroff et al (2022), these events are likely dominated by scattering (unlike the FRBs reported here).…”
supporting
confidence: 66%
“…This may indicate that many more such signals could be present in pulsar surveys which could have been missed in searches that did not increase the search window to sufficiently large values. This possibility was hinted at by Petroff et al (2022), where the authors speculate that a population of "not-so-fast radio bursts" (nsFRBs) with durations of between 100 ms and several seconds could be waiting to be discovered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible to study in great detail the spectrotemporal-polarimetric properties of the ≈ 4% of FRB sources found to repeat [16]. Most repeating FRB sources display a pulse-averaged LP ≈ 90-100% and nonvarying LP position angle (PA) across the burst profile [17].…”
mentioning
confidence: 99%